2022
DOI: 10.1111/jfbc.14097
|View full text |Cite
|
Sign up to set email alerts
|

Abelmoschus esculentus (L.) Moench improved blood glucose, lipid, and down‐regulated PPAR‐α , PTP1B genes expression in diabetic rats

Abstract: Abbreviations: ALT, alanine aminotransferase; AST, aspartate aminotransferase; AS160, AKT substrate of 160 kDa; Cho, cholesterol; DC, the diabetic control group; D + O200, the diabetic group treated with 200 mg/kg; D + M200, the diabetic group treated with the metformin chemical drug; D + Q50, the diabetic group treated with the 50 mg/kg quercetin; GLUT4, glucose transporter type 4; G6P, glucose 6-phosphate; HDL, High-density lipoprotein; HETEs, hydroxyeicosatctraenoic acid; IRs-1, insulin receptor substrate 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Two of the most well‐known flavonoids with blood sugar‐lowering effects are quercetin and isoquercetin (Schewe et al, 2008). A. esculentus helps reduce blood sugar, according to research (Kumar et al, 2013; Majd et al, 2018; Nasrollahi et al, 2022; Peng et al, 2016; Sabitha et al, 2011). The numerous flavonoids and polysaccharides found in A. esculentus can be examined in a lab setting to see how they work to lower blood sugar levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the most well‐known flavonoids with blood sugar‐lowering effects are quercetin and isoquercetin (Schewe et al, 2008). A. esculentus helps reduce blood sugar, according to research (Kumar et al, 2013; Majd et al, 2018; Nasrollahi et al, 2022; Peng et al, 2016; Sabitha et al, 2011). The numerous flavonoids and polysaccharides found in A. esculentus can be examined in a lab setting to see how they work to lower blood sugar levels.…”
Section: Discussionmentioning
confidence: 99%
“…The rats in the third group were diabetic rats which were treated with 80 mg/kg quercetin (Q). For 8 weeks, all treatments were given through gavage (Harmer et al, 2015; Jang et al, 2008; Kongkachuichai et al, 2013; Majd et al, 2018; Nasrollahi et al, 2022; Wein et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, okra is a truly promising natural ingredient to reduce inflammation in individuals with inflammation-predisposed disorders, with the potential to diminish C-reactive protein, IL-1 β , IL-6, and TNF- α [ 77 ]. In particular, flavonoid, one of the most pivotal components of okra, is responsible for the antioxidant and anti-inflammatory effects [ 39 ]. Compelling evidence suggests that the total flavonoid extract of flowers of Abelmoschus manihot (L.) Medicus alleviates acute lung injury in mice by inhibiting inflammation and oxidative stress [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total polyphenols, the major components in okra fruit extract [38], have several subclasses, such as flavonoid. Flavonoid compounds are the most imperative active ingredients in okra [39,40]. Previous studies have also reported the isolation of natural free flavonoid compounds and their derivatives from okra fruit [41][42][43].…”
Section: Introductionmentioning
confidence: 99%